Biopolitics, Essential Labor, and the Political-Economic Crises of COVID-19. (3rd March 2021) - Rose, Jeff
Abstract: Biopolitics is the power to control life. In the early global reactions to the COVID-19 pandemic, many people's daily labor functions have been placed into stark relief, with a tripartite typology forming between those labor functions that are "essential, " those labor roles that have been lost, and those that have transitioned to an online format. For those whose labor has maintained, as well as those who seek to return to pre-COVID-19 labor conditions, a crude biopolitical calculus takes place where the functioning of our capitalist political economy is weighed against the maintenance of life itself. The current pandemic exposes and highlights many of the unsustainable fault lines characteristic of contemporary capitalism, where the uneven exploitation of labor renders lives associated with some labor functions as more expendable than others. This places us in political-economic crisis, where we have choices to enact more just, equitable, and sustainable systems moving forward.